Revitalizing the Warehouse Management Logistics Processes Implementation in Land Transportation Manufacturing Companies: Revitalisasi Penerapan Proses Logistik Pada Warehouse Management Di Perusahaan Manufaktur Transportasi Darat - Vania Amanda; Sulastri Irbayuni (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
The logistics process in warehouse management is a crucial aspect in improving the operational efficiency of manufacturing companies. PT. XYZ requires a mature logistics strategy to support its production activities. The implementation of logistics activities often faces obstacles, both from internal and external factors, which can disrupt the supply chain flow. This activity explores the logistics planning and control strategies that have been implemented in the Warehouse Management System at PT. XYZ, and identifies the obstacles faced in logistics revitalization efforts. The activity uses a qualitative approach, with data collection through observation and interviews, including direct participation in service activities at the PT. XYZ warehouse. A revitalization program is proposed for the company, which involves improving logistics planning strategies and considering various factors that may cause errors in production or external factors such as natural disasters.